Speaking the same language - The effect of foreign origin teachers on students' language skills - Lisa Höckel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Population diversity arising from international migration does not only affect the labor market, but also its training ground - the classroom. While the economics literature studies the large and persistent achievement gap between native and foreign origin students, surprisingly little is known about the effect of having a foreign origin teacher on students' academic achievements. In this study, I investigate whether having a foreign origin teacher causally affects the language skills of students in German secondary school, holding constant both observed and unobserved factors related to academic outcomes. Exploring within-student variation in assignment to teachers, due to student mobility and teacher turnover, I am the first to show that foreign origin teachers significantly increase the reading comprehension of students. Most notable is the positive effect of foreign origin teachers who report a mother tongue other than German. They increase reading comprehension scores universally. Ruling out alternative explanations, I argue that bilingual teachers are particularly well-equipped in teaching languages to both native and foreign origin students.
Keywords: J13; J15; I24; 330; Academic achievement; language skills; matching; migration; teacher bias